KONSEP MODERASI BERAGAMA DALAM KITAB RISALAH AHLUSSUNNAH WAL JAMA'AH KARYA KH. HASYIM ASY'ARI SEBAGAI BASIS KURIKULUM PAI DI PERGURUAN TINGGI UMUM - Agus Salam; Asmaji Muchtar (Jurnal Manajemen Pendidikan, 2026)
Teaching materials often lack contextualization and responsiveness to contemporary issues facing students, such as religiously motivated hoaxes and digital polarization. As a result, a gap exists between the ideals of moderation advocated and students' competency in applying them, making the need for curriculum revitalization urgent.This study aims to develop a curriculum model for Islamic Religious Education (IRE) in public universities to address the challenges of intolerance. Grounded in social reconstruction theory, the model extracts values of religious moderation—tawassuth (moderation), tasamuh (tolerance), tawazun (balance), and i‘tidal (justice)—from Risalah Ahlussunnah wal Jama‘ah by KH. Hasyim Asy‘ari. Through content analysis, evaluation of the existing curriculum, and focus group discussions (FGDs), gaps between needs and current practices were identified. The result is a reconstructionist curriculum prototype featuring contextual materials and problem-based learning strategies. The model has been validated by experts and tested for readability, demonstrating high feasibility in shaping students as agents of moderation.